Quit Turnover and the Business Cycle: A Survey - Carlos Carrillo-Tudela; Melvyn Coles (Institute for the Study of Labor (IZA), 2015)
The focus of this chapter is to consider new developments in the search and matching literature where wages, quit turnover and unemployment are endogenously determined in economies with aggregate shocks. The aim of the discussion is not only to highlight possible market failures but also to explain how on-the-job search and employee turnover fundamentally affect our understanding of fluctuations in aggregate employment.
Keywords: J62; J63; J64; 330; business cycles; employer-to-employer transitions; search